Coverage and effectiveness of Kyasanur forest disease (KFD) vaccine in Karnataka, South India, 2005-10. - Gudadappa S Kasabi; Manoj V Murhekar; Vijay K Sandhya; Ramappa Raghunandan; Shivani K Kiran; Gowdra H Channabasappa; Sanjay M Mehendale (Public Library of Science (PLoS), 2013)
BACKGROUND: Kyasanur forest disease (KFD), a tick-borne viral disease with hemorrhagic manifestations, is localised in five districts of Karnataka state, India. Annual rounds of vaccination using formalin inactivated tissue-culture vaccine have been conducted in the region since 1990. Two doses of vaccine are administered to individuals aged 7-65 years at an interval of one month followed by periodic boosters after 6-9 months. In spite of high effectiveness of the vaccine reported in earlier studies, KFD cases among vaccinated individuals have been recently reported. We analysed KFD vaccination and case surveillance data from 2005 to 2010. METHODOLOGY/PRINCIPAL FINDINGS: We calculated KFD incidence among vaccinated and unvaccinated populations and computed the relative risk and vaccine effectiveness. During 2005-2010, a total of 343,256 individuals were eligible for KFD vaccination (details of vaccination for 2008 were not available). Of these, 52% did not receive any vaccine while 36% had received two doses and a booster. Of the 168 laboratory-confirmed KFD cases reported during this 5-year period, 134 (80%) were unvaccinated, nine each had received one and two doses respectively while 16 had received a booster during the pre-transmission season. The relative risks of disease following one, two and booster doses of vaccine were 1.06 (95% CI = 0.54-2.1), 0.38 (95% CI = 0.19-0.74) and 0.17 (95% CI = 0.10-0.29) respectively. The effectiveness of the vaccine was 62.4% (95% CI = 26.1-80.8) among those who received two doses and 82.9% (95% CI = 71.3-89.8) for those who received two doses followed by a booster dose as compared to the unvaccinated individuals. CONCLUSIONS: Coverage of KFD vaccine in the study area was low. Observed effectiveness of the KFD vaccine was lower as compared to the earlier reports, especially after a single dose administration. Systematic efforts are needed to increase the vaccine coverage and identify the reasons for lower effectiveness of the vaccine in the region.